Microencapsulation of Polyphenols from Orthosiphon stamineus Leaves Extracts using Polysaccharide and Protein - Sook, Fun Pang; Jolius, Gimbun; M. M., Yusoff; Luqman Chuah, Abdullah (2015)
This paper presents the Orthosiphon stamineus polyphenol extraction and microencapsulation study using whey protein isolate, gum arabic and maltodextrin. Polyphenol content was analysed using ultra-performance liquid chromatography. The highest yield of rosmarinic acid (38.70 mg RA/g DW) was obtained using 70% aqueous methanol, whereas the highest yield of sinensetin (261.21 µg Sin/g DW) and eupatorin (2.71 mg Eup/g DW) was obtained using isopropanol. Aqueous solvent such as 70% ethanol provide a broader range of polarity than the pure solvent, and hence enhances a simultaneous extraction of both methoxylated and hydroxylated compounds. It was found that microwave assisted extraction is capable to perform an efficient and very fast extraction of polyphenols within 2 minutes, compared to the ultrasonic assisted extraction which require 90 minutes. Microencapsulation of polyphenols from O. stamineus using WPI, maltodextrin and gum arabic has successfully reduced polyphenol degradation during spray drying. The highest polyphenol retention of rosmarinic acid (84.25%), sinensetin (83.96%) and eupatorin (85.61%) was achieved by microencapsulation using gum arabic. The gum arabic derived microcapsule has a smooth spherical surface which enhance particle flowability.